PREPARING FORWARD SPECIALISTS FOR PRESCHOOL EDUCATION: EUROPEAN EXPERIENCE - Kozak, Luydmila (Continuing Professional Education: Theory and Practice, 2019)
The article reveals the preparation of future pre-school education specialists in the UK, Sweden, Germany and Greece. It is shown that training of pedagogical staff is carried out in universities, institutes of higher education, institutes of pedagogy at universities, pedagogical colleges; found that differences in the training of future pre-school education specialists are reflected in the structure and content of educational programs; reviewed forms of organization of training of future specialists (lectures, seminars, practical classes, individual and collective projects, independent work) and interactive and problematic methods of teaching; is analyzed the practical training, which includes scientific research, designing and internship; has been determined that in the European countries common in the training of future specialists in preschool education is the flexibility of training programs, passing of pedagogical practice in special educational centers, scientific research direction of professional training, application of active teaching methods, information and communication technologies, and increased attention to the quality control of training. These aspects are promising for Ukrainian education.